The Experience of Foreign Countries in Teaching English in Preschool Educational Institutions - Ergasheva Gulnora Nematovna (International Journal on Integrated Education, 2022)
The paper aims to study recent research findings and literature on learning English as a foreign language in kindergarten. It has been a worldwide trend in the present century to lower the age of children's foreign language learning, and it is now common that children begin learning English as a foreign or a second language even before they start their formal primary education, at the age from zero to 7.